1997
DOI: 10.1111/j.1365-2044.1997.110-az0104.x
|View full text |Cite
|
Sign up to set email alerts
|

Oxygenation of patients undergoing ophthalmic surgery under local anaesthesia

Abstract: SummaryThe oxygenation of 30 patients undergoing elective ophthalmic surgery without sedation whilst breathing air was studied and was compared with two methods of oxygen supplementation. Arterial oxygen saturation, inspired and expired oxygen and carbon dioxide were analysed. The delivery of oxygen at 2 l.min ÿ 1 via nasal cannulae was shown to be superior to a method which directed oxygen from under the surgical drapes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
13
1

Year Published

1999
1999
2004
2004

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 12 publications
1
13
1
Order By: Relevance
“…Previous studies used fresh gas flows of 5-10 l.min À1 under the drapes [2,5,6]. In contrast to these studies, Risdall & Geraghty [8] suggested that low flow (2 l.min À1 ) of oxygen supplementation should be provided for all patients having Anaesthesia, 1999, 54, pages 683-702 Forum . .......................................................................................................................................................................................................................................... ophthalmic surgery under local anaesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies used fresh gas flows of 5-10 l.min À1 under the drapes [2,5,6]. In contrast to these studies, Risdall & Geraghty [8] suggested that low flow (2 l.min À1 ) of oxygen supplementation should be provided for all patients having Anaesthesia, 1999, 54, pages 683-702 Forum . .......................................................................................................................................................................................................................................... ophthalmic surgery under local anaesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…Fresh gas or oxygen supplementation under the drapes prevents hypoxia in such patients,1 2 but carbon dioxide exhaled by the patient escapes only partially through the ophthalmic drapes. The result is an increase in carbon dioxide in the ambient air surrounding the patient's head 3-5.…”
mentioning
confidence: 99%
“…It has been reported that during the investigative period, no significant differences were measured in MAP or HR in patients undergoing cataract surgery with local anesthesia. 1,3,21,22 Similarly, we did not observe any changes in SBP, DBP, MAP, or HR in our fentanyl group. Cardiovascular parameters were more stable in the fentanyl group than they were in the control group.…”
Section: Discussionmentioning
confidence: 51%
“…3,5,19 -21 It was reported that when oxygen support was provided via a nasal probe, no evidence of significant CO 2 accumulation or hypoxia under the surgical drapes was found in nonsedated patients. 5,22 An impaired permeability to CO 2 of the drapes, the presence of premedication, or opioid/sedative for sedation are the causes of CO 2 rebreathing, tachypnea, and an increase in peripheral SpO 2 during cataract surgery. 5 Expired CO 2 accumulates under the surgical drapes and patients breathe in the air containing the higher CO 2 concentration, resulting in an increased arterial CO 2 concentration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation